Tinjauan Aspek Legalitas Penggunaan Tanda Tangan Elektronik Pada Rekam Medis Elektronik di RS. X Kab. Tasikmalaya - Azzahra, Nazwa Salsabila; Sugiarti, Ida (Akademi Perekam dan Informasi Kesehatan Imelda, 2025)
The current era of information technology has penetrated various areas of life, including the health sector, where hospitals are expected to provide not only quality medical services, but also supporting services such as medical records. Medical records, which include patient identity, examination, treatment, actions, and services, have now been transformed into electronic medical records that include electronic signatures . The use of digital signature must meet the legality and security aspects with certification from official electronic certification organizers in Indonesia. This study aims to describe the legality and security aspects of the use of digital signature in medical records at RS. X The study used a qualitative descriptive method with a purposive sampling technique through interviews, observations, and documentation. The results showed that Digital signature at RS. X were divided into two: certified digital signature through BSrE used by doctors for important documents that have legal aspects, and uncertified digital signature used by other health workers with lower legal force. Although the hospital has implemented an information security system such as encryption, VPN, SSL, user whitelist, and routine system maintenance, there is no specific SOP regarding the use of digital signature. The main constraints are network disruptions and reliance on external systems such as BSrE, which can hamper healthcare delivery when systems are inaccessible, forcing hospitals to revert to manual procedures.